Analisis Tekno Eknonomi Pembuatan Pelet Ikan dari Limbah Sampah Organik di Kota Pekanbaru - ihsan hidayat ihsan (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
ABSTRACT The high volume of waste in Pekanbaru City especially organic waste make a new idea with it to use become a more useful like a fish feed. Fish feed or usually called with a fish pellets is very important in cultivation fish because fish pellets be first matter in cultivation fish cause make a higher cost 60-70% from production cost and than very right if used organic waste to make a fish pellets cause will be lower the production cost. Method in this research is Completely Randomized Design with three treatment and every treatment different with waste composition measure like a 5 Kg, 3 Kg, and 2 Kg. The other material in this pellets is chicken cutting waste, rice bran, EM-4 liquid, and tapioca flour. The results from laboratory is treatment A with 5 Kg waste be the best on the other treatment with 22,66% protein, carbohydrate 22,70%, fat 4,50%, fiber 13,23%, water content 12,88%, and ash content 14,67%. Cost of goods sold is Rp.7.000/Kg and break event point is 226,60 Kg/year. The conclusion is very advantage this pellets if production with use a organic waste. Keyword: Waste, Fish Pellets, Completely Randomized Design